Extraction and Quantification of Cyclic Di-GMP from P. aeruginosa - Roy, Ankita Basu (Bio Protoc, 2013)
Cyclic di-GMP (c-di-GMP) has emerged as an important intracellular signaling molecule, controlling the transitions between planktonic (free-living) and sessile lifestyles, biofilm formation, and virulence in a wide variety of microorganisms. The following protocol describes the extraction and quantification of c-di-GMP from Pseudomonas aeruginosa samples. We have made every effort to keep the protocol as general as possible to enable the procedure to be applicable for the analysis of c-di-GMP levels in various bacterial species. However, some modifications may be required for the analysis of c-di-GMP levels in other bacterial species.